Factores determinantes de las enfermedades diarreicas agudas en niños menores de 5 años: una revisión exhaustiva de la literatura - Apunte Ulloa, Alejandra Anabel (2025)
Acute diarrhoeal diseases (ADEs) in children under five years of age represent a significant public health concern worldwide, and the determinants of these diseases are multifaceted and include environmental, social, biological and behavioural aspects, For this reason, this study aimed to conduct an exhaustive review of the available scientific literature on the determinants of acute diarrhoeal diseases in children under 5 years of age, for which it was necessary to use a methodology based on a qualitative approach, through a systematic review meticulously following the guidelines provided by the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA), The main findings were that both environmental and socio-economic factors, together with the effectiveness of clinical and educational interventions, are critical in the development and management of these diseases, as the results obtained provide a solid basis for future research and for the development of more targeted and effective intervention strategies. In addition, clinical management and accurate diagnosis have been identified as key factors in the control of acute diarrhoeal diseases. It is concluded that the ability to rapidly identify pathogens allows the application of specific treatments that are effective in preventing serious infant health complications.